1997
DOI: 10.4319/lo.1997.42.2.0289
|View full text |Cite
|
Sign up to set email alerts
|

Pigment specific growth and grazing rates of phytoplankton in the central equatorial Pacific

Abstract: Dilution experiments were performed during two transects across

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
87
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 46 publications
9
87
4
Order By: Relevance
“…While the relationship between silicate and nitrate is identical in the eastern and central Pacific (Figure 8a Iron control may be exerted through a shift in the size spectrum of phytoplankton rather than through a shift in phytoplankton specific growth rate. While diatom community specific growth rates did not change significantly between surveys I and II [Latasa et al, 1997], the species composition and size distributions changed dramatically between these time periods [Iriarte and Fryxell, 1995]. Landry et al [1997] provide the convincing argument that differences observed between the two EqPac surveys were due to the combination of selective increase in growth rates of large phytoplankton (including diatoms) through selective grazing control of smaller phytoplankton (including diatoms).…”
Section: Role Of Iron and A Non-steady State Food Webmentioning
confidence: 94%
“…While the relationship between silicate and nitrate is identical in the eastern and central Pacific (Figure 8a Iron control may be exerted through a shift in the size spectrum of phytoplankton rather than through a shift in phytoplankton specific growth rate. While diatom community specific growth rates did not change significantly between surveys I and II [Latasa et al, 1997], the species composition and size distributions changed dramatically between these time periods [Iriarte and Fryxell, 1995]. Landry et al [1997] provide the convincing argument that differences observed between the two EqPac surveys were due to the combination of selective increase in growth rates of large phytoplankton (including diatoms) through selective grazing control of smaller phytoplankton (including diatoms).…”
Section: Role Of Iron and A Non-steady State Food Webmentioning
confidence: 94%
“…Samples (200 p1) of a mixture of 0.3 m1 H20 and 1 m1 extract were injected into a Varian 9012 HPLC system equipped with a Varian 9300 autosampler, a Timberh e column heater (26"C), and a Spherisorb 5 mm ODS2 analytical (4.6 X 250 mm) column and corresponding guard column. Pigments were detected with a Thermoseparation UV2000 detector (h = 436 and 450 nm) and analyzed after Wright et al (1991) and Latasa et al (1997). The HPLC method used cannot separate monovinyl chl a from divinyl chl a.…”
Section: Methodsmentioning
confidence: 99%
“…In these studies, size-fractionated rates for different groups were not reported, so primary production by, for example, picoplanktonic prymnesiophytes versus larger size fractions remains uncharacterized. Latasa et al (1997) showed that prymnesiophytes growth was balanced by grazing mortality Brown et al (2002) found that picophytoeukaryote growth was often, but not always, balanced by grazing in the Arabian Sea. This is important, because it indicates that large proportions of picoeukaryotic primary production are transferred to higher trophic levels (e.g., heterotrophic protists).…”
Section: Distribution Abundance and Activitiesmentioning
confidence: 99%